2007
DOI: 10.1291/hypres.30.875
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Arterial Stiffness by Aerobic Exercise in Elderly Subjects

Abstract: Arterial stiffness increases with aging (1), and is accelerated by common diseases such as hypertension, type 2 diabetes, and metabolic syndrome. Among various indices of arterial stiffness, pulse wave velocity (PWV) and the augmentation index (AI) are commonly used in clinical settings, because these parameters can be easily and noninvasively measured. PWV mainly reflects the vascular stiffness (2). On the other hand, AI is calculated based on the analysis of arterial pulse waveform. AI is not simply determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Nonetheless, the effects of exercise on arterial stiffness in elderly patients are conflicting due to a lack of research in this field. Certain studies show that mild to moderate aerobic exercise reduces arterial stiffness in 50-year old individuals [38], while other authors found no reduction in PWV in 60-year olds at risk of cardiovascular disease after a high-intensity exercise intervention [39]. This implies reduced vascular adaptability with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the effects of exercise on arterial stiffness in elderly patients are conflicting due to a lack of research in this field. Certain studies show that mild to moderate aerobic exercise reduces arterial stiffness in 50-year old individuals [38], while other authors found no reduction in PWV in 60-year olds at risk of cardiovascular disease after a high-intensity exercise intervention [39]. This implies reduced vascular adaptability with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the beneficial effects of regular moderate-intensity exercise on vascular stiffness are better documented. Regular exercise training is associated with beneficial effects on arterial elastic properties in various populations such as elderly subjects19 and individuals at high cardiovascular risk 20…”
Section: Discussionmentioning
confidence: 99%